The freedom of the right to religion of minorities : a comparative case study between Kenya and Egypt - Modirzadeh, Naz (University of Pretoria, 2006)
Prepared under the supervision of Dr. Naz Modirzadeh at the Department of Political Sciences, School of Humanities and Social Sciences, The American University in Cairo, Egypt